Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1016/s0009-9236(96)90204-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benazepril and nicardipine on microalbuminuria in normotensive and hypertensive patients with diabetes*

Abstract: Diabetic nephropathy is the most frequent cause of chronic renal failure. The onset of microalbuminuria in patients with diabetes mellitus, which seems to be related to blood pressure and the control of glycemia, is predictive of the development of true proteinuria. This multicenter, single-blind, randomized study examined the effects of benazepril and nicardipine on overnight microalbuminuria in 57 normotensive and 46 hypertensive diabetic patients. At the end of a 3-month placebo run-in period, the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Only one trial reported random sequence generation (14). One trial reported the method to generate the allocation sequence (15) (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one trial reported random sequence generation (14). One trial reported the method to generate the allocation sequence (15) (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…The test for heterogeneity was low ( P =0.73, I 2 =0%). Three papers (15, 19, 20) reported urine albumin excretion rate. The change in urine albumin excretion rate related outcome was not significantly different between the two treatment arms (MD=1.91μg/min; 95% CI: −10.3 to 14.12; P =0.76, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ACE inhibitors including benazepril showed beneficial effects in terms of reducing decline in GFR and the requirement for dialysis compared with ARB treatment in a long-term study in nondiabetic patients [117]. Benazepril and the CCB nicardipine demonstrated similar antihypertensive effects in diabetic patients; however, benazepril was more effective in reducing overnight microalbuminuria (p = 0.025) [118]. These findings are supported by further studies that have shown that use of a CCB alone does not slow progression of renal disease to the same extent as renin-angio tensin-aldosterone system antagonists, despite producing similar reductions in BP [119,120].…”
Section: Drug Profilementioning
confidence: 98%
“…Numerous reports have proved that treatment with ACE inhibitors reduces the urinary albumin excretion rate (UAER) in this particular category of patients (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, many of these trials were of rather short duration or contained only a small number of patients (2)(3)(4)(5)(6)(7)(8). When the effect of ACE inhibitors on UAER has been compared with that of other antihypertensive drugs, a more profound reduction has often been achieved with ACE inhibition (2,7,8,10).…”
mentioning
confidence: 99%
“…However, many of these trials were of rather short duration or contained only a small number of patients (2)(3)(4)(5)(6)(7)(8). When the effect of ACE inhibitors on UAER has been compared with that of other antihypertensive drugs, a more profound reduction has often been achieved with ACE inhibition (2,7,8,10). Demonstration of a reduction in UAER, even after correction for changes in blood pressure (BP) (17), and two large studies of the short-acting ACE inhibitor captopril (9,11) also implicate that pharmacological inhibition of ACE confers renoprotective effects that are independent of changes in BP in normotensive patients with type 1 diabetes.…”
mentioning
confidence: 99%